Separation efficiency maximization in acoustofluidic systems: study of the sample launch-position. Issue 68 (20th November 2018) - Vitali, Valerio; Yang, Tie; Minzioni, Paolo
Abstract : We theoretically and numerically show how to optimize the separation-efficiency of acoustofluidic systems by a non-trivial selection of sample-injection position. Abstract : The development of lab-on-chip microfluidic systems based on acoustic actuation, and in particular on the acoustophoretic force, has recently attracted significant attention from the scientific community thanks, in part, to the possibility of sample sorting on the basis of both geometrical and mechanical properties. It is commonly recognized that sample prefocusing and launch-position optimization have a substantial effect on the performance of these systems but a clear explanation of how these two parameters influence the system efficiency is still missing. In this manuscript we discuss the impact of both the sample launch position and the sample distribution at the input by the theoretical analysis of a simplified system and by numerical simulations of realistic configurations. The results show that the system performance can be greatly improved by selecting the proper microchannel dimensions and sample-launch position, offering relevant guidelines for the design of micro-acoustofluidic lab-on-chip devices.